Real Options Valuation The Importance of Interest Rate Modelling in Theory and Practice - Schulmerich, Marcus; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book analyzes real options valuation for non-constant versus constant interest rates using simulations and historical backtesting. It provides a systematic analysis and compares real options valuation using constant interest rates and the implied forward rates with methods that simulate interest rates stochastically. Real options are investigated and combined with various pricing tools and stochastic term structure models. Interest rates for real options valuation are simulated by using stochastic term structure models (Vasicek, Cox-Ingersoll-Ross, Ho-Lee, and Hull-White one-factor and two-factor models) and by using implied forward rates. All necessary theory is provided in the book. The analyses were conducted using a proprietary computer simulation program. All results are explained in detail and rules are derived for application in Corporate Finance practice. The major change in this second edition is the expanded number of tested scenarios. The second edition contains an expanded number of tested scenarios covering the time period of the financial crisis 2008, one of the worst stock market crashes in history. The findings confirm the results provided in the first edition.
Real Options in Theory and Practice -- Stochastic Models for the Term Structure of Interest Rates -- Real Options Valuation Tools in Corporate Finance -- Analysis of Various Real Options in Simulations and Backtesting -- Summary and Outlook.
Keywords: Economics; Finance; Distribution (Probability theory).; Banks and banking; Economics/Management Science; Financial Economics; Finance /Banking.; Quantitative Finance; Probability Theory and Stochastic Processes